Nghiên cứu thành phần hóa học, chi số hóa lý và hoạt tính sinh học của tinh dầu quả phật thủ Việt Nam - Lợi, Nguyễn Văn; Minh Tú, Nguyễn Thị; Hòa, Hoàng Đình (Vietnam Journal of Chemistry, 2015)
The Hoai Duc Buddha’s fruit oil is obtained by alluring steam distillation and dried with Na2SO4. By using the GC- MS method, 40 chemical components were identified in the Hoai Duc Buddha’s fruit oil, from which hydrocarbons accounted for 38.29 % (monoterpene: 29.27 %, sesquiterpene: 8.32 %) and oxygenated components accounted for 60.04% (aldehyde: 21.01 %, alcohol: 21.34 %, ester: 12.55 %, oxide: 2.80 %, acid: 2.34 %). That has been identified the density in 20 oC is 0.835, acid index is 0.655 (mg KOH/g) and esters index is 0.726 (mg KOH/g). The DPPH methods having antioxidant activity have identified oil 41.16±0.23 % with the Hoai Duc Buddha’s fruit oil. Besides using agar diffusion method identifying antimicrobial activity of three oils on microorganisms Staphylococcus aureus, Escherichia coli, Salmonella typhi and Bacillus cereus.